ANTINEOPLASTIC EXTRAVASSIONS IN A CHEMOTHERAPY AMBULATORY IN THE STATE OF MARANHÃO - Silva Falcão, Bruna Caroline (2023)
OBJECTIVE: to evaluate the number of adverse events such as extravasation of antineoplastic agents in cancer patients undergoing treatment at a chemotherapy outpatient clinic of a CACON. METHODS: this is a cross-sectional transcriptional study with a secondary quantitative approach, based on secondary data on adverse events recorded in the notification book of a CACON High Complexity Oncology Center in São Luís, Maranhão. RESULTS: 19 notifications of extravasation were recorded, with the highest number of records in the months of February and April, in both sexes, aged over 60 years, with prostate cancer and breast cancer, carboplatin drugs, docetaxel and paclitaxel, in an interval of 28 days, using jelco, on the upper limbs, with signs and symptoms of pain and burning and with quick action by the team. CONCLUSION: the HCAB chemotherapy outpatient clinic has a low rate of extravasation in relation to its annual number of consultations.